The Pension System in Iran : Challenges and Opportunities, Volume 2. Technical Appendix - World Bank (Washington, DC, 2013)
The present report evaluates the Iranian pension system and proposes a series o f policy interventions to improve outreach, financing mechanisms, incentives, equity, and management. It has been prepared at the request o f the Management and Planning Organization. Given data constraints, the analysis concentrates primarily on the Social Security Organization and the Civil Servants Retirement Organization, the two main pension funds. Occupational funds and non- contributory regimes are surveyed only briefly. The need to look more closely at these schemes in the near future i s emphasized. The report i s organized in eight sections. Section 1 presents the background o f the study. Section 2 provides a general overview o f the Iranian pension system. Sections 3 and 4 present detailed assessments of the Social Security Organization and the Civil Servants Retirement Organization. Section 5 concentrates on the tax treatment o f retirement savings. Section 6 proposes a framework for guiding pension reform, presents a typology o f pension mechanisms, and reviews international experiences. On the basis o f this framework, Section 7 outlines strategic directions for reforming the Iranian pension system and analyzes the financial and fiscal implications. Finally, Section 8 discusses the political economy o f pension reform and recommends necessary steps for the design and implementation o f a successful reform program.